2011
DOI: 10.4103/0971-4065.85481
|View full text |Cite
|
Sign up to set email alerts
|

Renal allograft pathology with C4d immunostaining in patients with graft dysfunction

Abstract: Renal allograft biopsy is the gold standard for diagnosis of rejection. Incorporation of C4d as a marker for humoral rejection is a major addition for Banff Schema, 2005. We evaluated the pattern of C4d staining in indicated renal allograft biopsies from January 2005 to December 2009. Of the 67 biopsies analyzed, 21 were C4d-positive. They were 11 cases of acute rejection, seven chronic rejection and one biopsy each of acute tubular necrosis, BK virus nephropathy and normal biopsy. Morphologic features like pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
6
0
Order By: Relevance
“…In renal allografts, findings other than rejection can be seen and can also be a cause of graft dysfunction. In our 60 cases, ACR was documented in 7 (11.6%) cases, cyclosporine drug toxicity in 5 (13). As AMR can be the cause of graft dysfunction even many years of renal transplant, thus in every case, a biopsy must be submitted for C4d staining.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…In renal allografts, findings other than rejection can be seen and can also be a cause of graft dysfunction. In our 60 cases, ACR was documented in 7 (11.6%) cases, cyclosporine drug toxicity in 5 (13). As AMR can be the cause of graft dysfunction even many years of renal transplant, thus in every case, a biopsy must be submitted for C4d staining.…”
Section: Discussionmentioning
confidence: 77%
“…In studies performed during the early 21st century, a frequency of AMR in background of CAN was reported in the range of 4.4% to 61% (21,24,40). In 2005 and onwards, AMR in background of CAN was observed in 5.1% to 50% of cases (6,13,(41)(42)(43). Yoon et al reported 5.1% of biopsies, and this difference is probably due to the inclusion of only protocol (42).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Histopathology is the gold standard for diagnosing graft rejection after transplantation [34]. There are the infiltration of inflammatory cells to portal area including activated lymphocytes, neutrophils and acidophils, inflammation of endotheliocytes under the portal vein and central vein, and the inflammation and injury of the bile duct in the acute rejection of liver transplantation [35, 36].…”
Section: Discussionmentioning
confidence: 99%